Solve 3*m - 1 = -5*n - 12, -5*m - 11 = n for n.

-1

Solve 5 = 5*i + 9*j - 4*j, j + 15 = 3*i for i.

4

Solve -2*p + 8 = 4*b, 5*b = 6*p - 9*p + 8 for p.

-4

Solve f - 3*b = -3, -5*f - 14*b + 17 = -13*b for f.

3

Solve 2 = 2*j + 4*r, 4*r + 9 = j + 2 for j.

3

Solve -5*k - 4*t - 11 = 0, -4*k + t + 2*t + 16 = 0 for k.

1

Solve 18 = -3*p - 3*s, 5*s = -p - 25 + 11 for p.

-4

Solve -4 = -3*i + 3*w - 1, 0 = -i - 4*w - 4 for i.

0

Solve -2*r - 14 = 2*g + 2, r = -4*g - 23 for r.

-3

Solve 0*z + z - 20 = -5*a, 3*a - z - 12 = 0 for a.

4